(untitled) (Revista de Ciências Agroveterinárias, 2018)
Genotype and plant nutrition influence the production of physiological qualities in maize seeds, and the use of vigor tests under stress conditions allows for the identification of superior genotypes. The aim of this study was to verify the effect of covered nitrogen fertilization on the physiological quality of seeds from 12 half-sib maize families, with or without saline stress. Seeds were used from plants that were growing with two levels of top dressed nitrogen fertilization (0; 150 kg ha-1), in the 2012/13 growing season, at Gurupi, in the state of Tocantins. In the laboratory, two experiments were conducted: one without and another with saline stress (KCl – 16.73 g L-1). The experimental design was fully randomized, with a factorial arrangement (12x2x2) and four replications. The following tests were carried out: germination, length and dry weight of seedling. The effects of topdressed nitrogen were more visible in the conditions of saline stress on the seeds. In this situation, when seeds were produced without topdressed N the half-sib L8 showed higher: total length (15.3 cm), root length (9.54 cm) and aerial part length (5.75 cm), and dry weight of roots (26 mg seedling-1) and aerial part (28 mg seedling-1). The half-sib L9 had shown significant (positive) influence from the use of topdressed N when germination was carried out with saline stress. The concentration of KCl (16.73 g L-1) promoted significant decreases in the germination and vigor of the seeds, however, it allowed for the visualization of the effect of covered nitrogen fertilization. In conditions without topdressed N and saline stress at germination, the half-sibs P6 and L8 showed superiority.